Modeling and Performance Analysis of Throughput-Received Power Relationship for Indoor Wireless Mesh Network - Zakaria, Mohd Sharim; Ahmad, Mohd Riduan; Johal, M. Syahrir; Suaidi, M. Kadim (2010)
In Wireless Mesh Network (WMN) the mesh nodes (APs) are configured with the same frequency channel creates a phenomenon called as co-channel interference. The purpose of selecting the same frequency channel is to make sure all the mesh nodes can talk each other within the frequency range. In order to study the effects of this phenomenon together with multipath fading for indoor environment, we have setup a wireless mesh network operating at 2.4GHz inside a 4-floors faculty building. Extensive measurement campaigns have been conducted at each floor. To observe the effects of these phenomena at the application layer perspective, we measure the network throughput and mapped it to the physical layer performance parameter; received power. The relationship between the application and physical layers performance parameters is modeled numerically and the results are analyzed. One interesting finding is that the empirical relationship model for wireless mesh network does not follow the common exponential models as known in Wireless Local Area Network (WLAN). We can say that the throughput drop is too small and can be neglected and the average throughput is at 1.53Mbps over all received powers. The result shows that the effects of both co-channel interference and multipath are very severe and need to be tackled properly in wireless mesh network design and deployment.